2019
DOI: 10.1039/c9ra01360a
|View full text |Cite
|
Sign up to set email alerts
|

One-pot route to graft long-chain polymer onto silica nanoparticles and its application for high-performance poly(l-lactide) nanocomposites

Abstract: A facile “one-pot” synthetic route is used to modify SiO2 nanoparticles with a long-chain polymer, and to prepare high-performance poly(l-lactide) nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Polymers 2020, 12, x FOR PEER REVIEW 3 of 20 been reported that silica disperses well in PLA and results in improved mechanical and thermal properties, and also enhances the crystallinity of the structures [30][31][32]. Moreover, since silica is reported to have high silanol groups, siloxane bridges, and hydroxyl groups [12], it can be easily functionalized, opening pathways for several applications such as biomedical, separation, catalysis, and sensors [17,33].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers 2020, 12, x FOR PEER REVIEW 3 of 20 been reported that silica disperses well in PLA and results in improved mechanical and thermal properties, and also enhances the crystallinity of the structures [30][31][32]. Moreover, since silica is reported to have high silanol groups, siloxane bridges, and hydroxyl groups [12], it can be easily functionalized, opening pathways for several applications such as biomedical, separation, catalysis, and sensors [17,33].…”
Section: Introductionmentioning
confidence: 99%
“…When 1 wt% F G is added into PLA matrix, there is a significant improvement in value of Δ H m is noticed which demonstrates that F G enhanced the formation of PLA crystals. It is fact that the addition of F G enhanced the crystalline ability of PLA 29 . For DCP modified samples T g , T m1, T m2 , and T cc are almost unchanged with PLA/1 F G, whereas the values of Δ H m and Δ H cc progressively reduced to around ~30.8 and ~ 23.1 J/g (PLA/D/3 F G), respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Bioderived polylactic acid (PLA) features good biodegradability ( Xie et al., 2020 ; Zhang et al., 2020 ), high transparency, high mechanical strength, low shrinkage, and ease of processability, making it one of the most commercially valuable bio-sourced polymers ( Vahabi et al., 2018 ; Wen, 2019 ). As a result, PLA has been extensively used in packaging, electric and electronic, transport fields, and so forth.…”
Section: Introductionmentioning
confidence: 99%